Genetic Variation in Male Mate Choice for Large Females in Drosophila melanogaster - Grace S. Freed; Isabella G. Martinez; Avigayil Lev; Ana‐Maria Anthony Cuadrado; Alison Pischedda (Ecology and Evolution)
ABSTRACT Males in many species show courtship and mating preferences for certain females over others when given the choice. One of the most common targets of male mate choice in insects is female body size, with males preferring to court and mate with larger, higher‐fecundity females and investing more resources in matings with those females. Although this preference is well‐documented at the species level, less is known about how this preference varies within species and whether there is standing genetic variation for male mate choice within populations. We used hemiclonal analysis in the fruit fly, Drosophila melanogaster, to test for heritable genetic variation in pre‐ and postcopulatory components of male mate choice for large females. We found additive genetic variation for both forms of male choice: Males from different hemiclone lines varied in the strength of their courtship preferences for large females and the degree to which they extended matings with large females. Although males from hemiclone lines with stronger courtship preferences for large females were more likely to mate with those females, there was no genetic correlation between pre‐ and postcopulatory components of male mate choice, suggesting that they are under independent genetic control. Genetic variation in male mate choice may be widespread, potentially impacting the fitness of both sexes and the adaptive evolution of populations.